Kyphoplasty Increases Vertebral Height, Decreases Both Pain Score and Opiate Requirements While Improving Functional Status. Issue 3 (25th October 2013) - Tolba, Reda; Bolash, Robert B.; Shroll, Joshua; Costandi, Shrif; Dalton, Jarrod E.; Sanghvi, Chirag; Mekhail, Nagy
Abstract Vertebral compression fractures can result from advanced osteoporosis, or less commonly from metastatic or traumatic insults to the vertebral column, and result in disabling pain and decreased functional capacity. Various vertebral augmentation options including kyphoplasty aim at preventing the sequelae of pain and immobility that can develop as the result of the vertebral fractures. The mechanism for pain relief following kyphoplasty is not entirely understood, and the restoration of a portion of the lost vertebral height is a subject of debate. We retrospectively reviewed radiographic imaging, pain relief, analgesic intake and functional outcomes in 67 consecutive patients who underwent single‐ or multilevel kyphoplasty with the primary goal of quantifying the restoration of lost vertebral height. We observed a mean of 45% of the lost vertebral height restored postprocedurally. Secondarily, kyphoplasty was associated with significant decreases in pain scores, daily morphine consumption and improvement in patient‐reported functional measures.